First Order Temperature Dependent Phase Transition in a Monoclinic Polymorph Crystal of 1,6-Hexanedioic Acid: An Interpretation Based on the Landau Theory Approach - Fun, Hoong Kun; Chantrapromma, Suchada; Ong, Lye Hock (MDPI, 2014)
Crystals of 1,6-hexanedioic acid (I) undergo a temperature-dependent reversible phase transition from monoclinic P21/c at a temperature higher than the critical temperature (Tc) 130 K to another monoclinic P21/c at temperature lower than Tc. The phase transition is of first order, involving a discontinuity and a tripling of the b-axis at Tc whereas the other unit cell parameters vary continuously. The transition is described by the phenomenological Landau theory. The crystal structure analyses for data collected at 297(2) K and 120.0(1) K show that there is half of a molecule of (I) in the asymmetric unit at 297(2) K whereas there are one and a half molecules of (I) in the asymmetric unit at 120.0(1) K. At both temperatures, 297(2) and 120.0(1) K, intermolecular O-H···O hydrogen bonds link the molecules of I into infinite 1D chains along [101] direction. However there are significantly more O-H···O hydrogen bonds presented in the 120.0(1) K polymorph, thereby indicating this phase transition is negotiated via hydrogen bonds. The relationship of the conformational changes and hydrogen bonding for these two polymorphs are explained in detail.